2013
DOI: 10.1093/eurheartj/eht189
|View full text |Cite
|
Sign up to set email alerts
|

SCORE performance in Central and Eastern Europe and former Soviet Union: MONICA and HAPIEE results

Abstract: AimsThe Systematic COronary Risk Evaluation (SCORE) scale assesses 10 year risk of fatal atherosclerotic cardiovascular disease (CVD), based on conventional risk factors. The high-risk SCORE version is recommended for Central and Eastern Europe and former Soviet Union (CEE/FSU), but its performance has never been systematically assessed in the region. We evaluated SCORE performance in two sets of population-based CEE/FSU cohorts.Methods and resultsThe cohorts based on the World Health Organization MONitoring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
4
29
0
3
Order By: Relevance
“…The test results of MONICA and SEPHAR survey showed that among men the average risk of death, according to the SCORE scale, is around 5%, whereas for women it was much lower (around 2%). 49,50 In the present study, similar results were obtained. However, the results from the HAPIEE study (conducted in the Czech Republic, Poland and Russia) showed that the mean value representing the risk of death for men was approx.…”
Section: Discussionsupporting
confidence: 90%
“…The test results of MONICA and SEPHAR survey showed that among men the average risk of death, according to the SCORE scale, is around 5%, whereas for women it was much lower (around 2%). 49,50 In the present study, similar results were obtained. However, the results from the HAPIEE study (conducted in the Czech Republic, Poland and Russia) showed that the mean value representing the risk of death for men was approx.…”
Section: Discussionsupporting
confidence: 90%
“…The historic dynamics of the total death rates demonstrates the certain role of the socio-economic disasters for both total and CV mortality, for instance in 90s after the dissolution of the Soviet Union and a default of 1998 (25,28,30), but most probably it makes a sense exceptionally in case of the larger dramatic economic events with the pronounced impoverishment of the population and degradation of the social life with significant changes in a lifestyle which was previously confirmed in both MONICA and HAPIEE studies that observed different populations in the Eastern Europe (1,29,30). The Russian mortality trend documents the dramatic increase of death rates after 1988 at the phase of the Soviet degradation (with a fold GDP decline of −0.36) and the further drop after 2002 with the lowest GDP (PPP) per capita of 8,539.00 U.S. dollars in 1998 growing up to actual $23,292.91 in 2016 amid broad reforms of both the Russian economics and public health system.…”
Section: Summary and Discussionmentioning
confidence: 56%
“…The smoking (17.3% of screened with a 2,786 cig a year; 63.2% of male and 9.1% of female; 70.6% in the trial; a contribution to mortality is about 29%), excessive alcohol consumption (1.8% of screened with a 11.6 L per year mostly of beer and vodka; 50.6% in the trial; about 70% consumed strong alcoholic beverages; responsible for 25.6% of CV deaths in male and 15.4% in female), unhealthy diet with insufficient consumption of fruits, vegetables, sea food, unsaturated fat, and proteins (mean 12% of the daily consumption) with abundance of carbohydrates/ sugar (up to 57% of diet), saturated and trans fats (up to 29-40% of the energy) including palm oil, butterfat, mayonnaise, and junk processed red meat), psychosocial factors (75% of Russians are not adapted to new living conditions, 20%-stress, 11.7%-anxiety, and 9.6%-depression) and physical inactivity (19.6% of screened; at least 73.9% of men and 74.8% of women) remain the major modifiable risk factors. They, in turn, affect (see Figure 3) (5,14,15,(17)(18)(19)(20)(21)(22)(25)(26)(27)(28)(29)(30) such risk factors as dyslipidemia (86.7% in the trial), obesity (16.7% of screened; mean BMI in the trial was 28.4), and hypertension (about 40.8% suffered; 86.1% in the trial), which is relevant to findings of the EUROASPIRE IV trial (31,32) in the European population, and screening studies of the Russian Cardiovasc Diagn Ther 2017;7(1):60-84 cdt.amegroups.com 1980 1982 1984 1986 1988 1990 1992 1994 1996 1998 Total mortality per 1,000, 2012…”
Section: Cardiovascular Mortality and Major National Risk Factorsmentioning
confidence: 99%
“…The SCORE was validated against CVD mortality in Central and Eastern Europe and former Soviet Union countries, using prospective data from the WHO MONICA project and HAPIEE study. In the MONICA cohort, the SCORE showed only moderate discriminatory ability (aROC of 0.54-0.69) and good calibration in Czech Republic, Poland and Lithuania, but overestimation of fatal CVD in Russia [26].…”
Section: Recent Trends In Cardiovascular Risksmentioning
confidence: 93%
“…Developing countries have different progresses in adopting the concept of cardiovascular risk assessment ( Other countries carried out a validation study to see if the existing risk scores performed well in predicting cardiovascular events in its population and further recalibrated the risk scores [24][25][26]. For example, the office-based Framingham risk equations were recalibrated in 46,674 participants in the Golestan Cohort in North-East of Iran and the authors found that the risk score performed reasonably well in predicting CVD mortality (aROC of 0.76-0.79) and overestimated CVD risk in men [25].…”
Section: Recent Trends In Cardiovascular Risksmentioning
confidence: 99%